An environmentally benign ionic liquid based formulation for enhanced oil spill remediation: Optimization of environmental factors - Shah, M.U.H. (Elsevier B.V., 2020)
Formulations based on ionic liquids (ILs) have emerged as potential alternatives to conventional dispersants for remediating the effect of oil spills. However, the performance of such IL formulations is greatly affected by various environmental factors. The present study developed a model that correlates the wave-mixing energy, temperature and salinity with the dispersion effectiveness for a formulation comprising an IL surfactant and a biosurfactant using response surface methodology. The experimental results were fitted with a second-order quadratic model; the analysis of variance showed good correlation between the experimental and predicted data with a R2 value of 0.9968. The maximum dispersion effectiveness was found to be 88.4 at the optimized conditions of a stirring rate of 242 rpm, temperature of 28.3 Â°C and salinity of 3.4 wt with an experimental error of <2.0. Crude oil samples dispersed at these optimized conditions were examined by optical microscopy and dynamic light scattering, and fine droplets with sizes of <300 nm were observed. The results of this work will improve the understanding of the effects of specific environmental factors on this new formulation and assist in oil spill response planning and decision making. Â© 2020 Elsevier B.V.